Pharmacology education in the perspective of pharmaceutical promotion: Bangladesh experience - Johora, Fatema; Rahman, Md. Sayedur (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
The medical practice has become complex and challenging because of the entry of newer medicines and technologies. The key objective of pharmacology teaching-learning activities is to make graduates enable to select medicines by appraising safety, efficacy, cost and suitability. Promotional activities conducted by pharmaceutical industries deleteriously affect physicians’ prescribing practice. The present research was conducted with an attempt to explore current academic documents related to Pharmacology education in Bangladesh. The curriculum (pharmacology portion of undergraduate medical curriculum), books of pharmacology (preferred by the pharmacologists), and written question papers (of last five years from all universities) were evaluated by searching certain key phrases. The curriculum of undergraduate course did not give adequate emphasis on issues related to the pharmaceutical promotion. Ethical issues and ‘critical appraisal skill’ are not mentioned in the pharmacology books, and not appear in the written examinations.